The Inter-Asia cultural studies reader - Chen, Kuan-Hsing; Chua, Beng Huat (Routledge, 2007)
Asian Cultural Studies or Cultural Studies in Asia is a new and burgeoning field, and the Inter-Asia Cultural Studies Journal is at its cutting edge. Committed to bringing Asian Cultural Studies scholarship to the international English speaking world and constantly challenging existing conceptions of cultural studies, the journal has emerged as the leading publication in Cultural Studies in Asia.